2015
DOI: 10.1016/j.neubiorev.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the neurobiology of non-suicidal self-injury from the perspective of the Research Domain Criteria Project

Abstract: Non-suicidal self-injury (NSSI) commonly starts in adolescence and is associated with an array of negative outcomes. Neurobiological research investigating NSSI is in its early stages and most studies have examined this behavior within the context of specific diagnoses. However, the Research Domain Criteria (RDoC) initiative encourages researchers to examine brain-behavior relationships across diagnoses. This review on the neurobiology associated with NSSI is organized using the domains proposed by RDoC: Negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 96 publications
0
27
1
Order By: Relevance
“…It may well be that the proposed DSM 5 definition provides a chance to use a uniform definition, which will increase comparability between studies. This will also serve future research on the neurobiology of NSSI, as the suggested diagnostic criteria lend itself to be explored using a Research Domain Criteria approach [51]. Given the high prevalence of NSSI in adolescents, further treatment studies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…It may well be that the proposed DSM 5 definition provides a chance to use a uniform definition, which will increase comparability between studies. This will also serve future research on the neurobiology of NSSI, as the suggested diagnostic criteria lend itself to be explored using a Research Domain Criteria approach [51]. Given the high prevalence of NSSI in adolescents, further treatment studies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have examined the differentiation between the BAS subscales in relation to self-injury, the frequency of prior NSSI behaviors was found to be associated with greater trait BAS-Fun Seeking subscale scores (willingness to approach rewards impulsively) in two studies and with greater trait BAS-Drive subscale scores (a general tendency to approach rewards) in one study (Cerutti et al, 2012;Jenkins et al, 2013). There is a lack of research examining reward sensitivity in parallel with longitudinal assessments of NSSI thoughts or behaviors, particularly when accounting for maltreatment (Westlund et al, 2015).…”
Section: Reward Sensitivity As a Risk Factor For Nssimentioning
confidence: 99%
“…That is, moving beyond a focus on self-reinforcement of NSSI solely at the physiological level to a study of changes in their associated neurocircuitry over the course of NSSI may yield specific, modifiable targets of intervention. The study of the neural processes underlying NSSI, however, is still in its infancy, and has predominantly involved assessing this behavior within the context of psychiatric diagnoses rather than as a transdiagnostic clinical phenomenon (Westlund Schreiner et al, 2015). One study of individuals who had engaged in NSSI (Osuch et al, 2014) observed a positive association between degree of relief after a physically aversive stimulus and blood oxygen level-dependent (BOLD) response in the dorsal striatum, a brain region involved in processing rewards (Everitt and Robbins, 2013; O’Doherty et al, 2004) and habitual behavior formation (Schiltz, 2006).…”
Section: Nssi As a Repetitive Behavior That Becomes Fixed Over Timementioning
confidence: 99%